Barriers and facilitators of physical activity for individuals with depression: a systematic review within the socio-ecological model framework - Duina, Marta; Santi, Giampaolo; Carraro, Attilio (Frontiers in Sports and Active Living, 2025)
IntroductionMental health disorders affect approximately one in every eight individuals globally, with many facing limited access to care, social exclusion, and stigma. Depression, in particular, is a leading cause of disability and has profound effects on individuals and society. Physical activity (PA) has emerged as a promising non-pharmacological intervention to alleviate depressive symptoms and promote well-being. However, people with depression often encounter substantial barriers to PA participation, exacerbating sedentary behaviors and health disparities.MethodsThis systematic review synthesizes findings from 14 peer-reviewed studies (n = 25,375 participants examining barriers and facilitators to PA engagement among individuals with clinically diagnosed depression. Studies included both qualitative and quantitative designs and were identified through searches in PubMed, ProQuest, Web of Science, Scopus, Cochrane Library, and PsycINFO. Inclusion criteria focused on studies involving participants with depression, as defined by DSM criteria, and reporting on PA-related barriers or facilitators. Studies involving healthy populations or comorbid severe physical conditions were excluded.Results and DiscussionAdopting Bauman's socio-ecological model, there view categorizes determinants across multiple levels: individual (e.g., motivation, symptoms), interpersonal (e.g., social support), environmental (e.g., access to facilities), and policy/cultural level (e.g., educational status). Findings underscore the importance of multi-level, tailored interventions to address the complex challenges faced by individuals with depression in engaging in PA. Recommendations are provided to guide the development of inclusive, context-sensitive strategies that promote mental health through PA.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025631996, identifier CRD42025631996.